SOCS-JAK-STAT inhibitors and SOCS mimetics as treatment options for autoimmune uveitis, psoriasis, lupus, and autoimmune encephalitis - Pandey, Rahul; Bakay, Marina; Hakonarson, Hakon (Frontiers in Immunology, 2023)
Autoimmune diseases arise from atypical immune responses that attack self-tissue epitopes, and their development is intricately connected to the disruption of the JAK-STAT signaling pathway, where SOCS proteins play crucial roles. Conditions such as autoimmune uveitis, psoriasis, lupus, and autoimmune encephalitis exhibit immune system dysfunctions associated with JAK-STAT signaling dysregulation. Emerging therapeutic strategies utilize JAK-STAT inhibitors and SOCS mimetics to modulate immune responses and alleviate autoimmune manifestations. Although more research and clinical studies are required to assess their effectiveness, safety profiles, and potential for personalized therapeutic approaches in autoimmune conditions, JAK-STAT inhibitors and SOCS mimetics show promise as potential treatment options. This review explores the action, effectiveness, safety profiles, and future prospects of JAK inhibitors and SOCS mimetics as therapeutic agents for psoriasis, autoimmune uveitis, systemic lupus erythematosus, and autoimmune encephalitis. The findings underscore the importance of investigating these targeted therapies to advance treatment options for individuals suffering from autoimmune diseases.